Acute abdominal pain as a manifestation of acute appendicitis in a 15-year-old adolescent: A case report - Dzaka Ogan Amirudin Lutfi; Raden Tri Gunawan Wibowo; Fadli Robby Amsriza; Muhamamd Hisyam Syafii (Nur Science Institute, 2026)
Acute abdominal pain is a common complaint in pediatric and adolescent patients, frequently encountered in the emergency department, with acute appendicitis being the primary cause. However, the diagnosis of appendicitis in adolescents is often challenging due to atypical clinical presentations, potentially leading to delayed treatment. This case report describes a 15-year-old female patient with complaints of right lower abdominal pain lasting for one week, accompanied by fever and nausea. Physical examination revealed tenderness at McBurney's point and a positive Rovsing's sign. Laboratory results showed leukocytosis with neutrophilia, microcytic hypochromic anemia, and increased prothrombin time and INR. The patient underwent open appendectomy under general anesthesia, and postoperative care included pain management and antibiotics. Monitoring of vital signs and surgical wound condition was performed well. This case report emphasizes the importance of a comprehensive clinical diagnostic approach to acute abdominal pain in adolescents, early detection of acute appendicitis to prevent serious complications such as perforation and sepsis, and optimal postoperative follow-up to speed recovery.